Ethics in academics and organizations: a fundamental ingredient for national development - Ransome, Barr. Owoka Olugbenga; Oluyemi, Ayodeji Esther (Journal of Social Review and Development, 2022)
Ethics can be described as moral principles, guidelines that explain rules and regulations people live by to make sure the right things are done, in various setting whether in government establishment or private. Ethics nowadays is a subject of discussion that has attracted serious debate. This study is intended to assess the ethical performances of some selected individuals in academics organization. Low productivity, indiscipline/violation of rules and regulations, weak control and corruption has been observed as results of unethical practices. This research employs general interview as well as semi-structured Interviews, which were flexible, sensitive to the social interaction within human relations. The research shall focus on the significant of ethical performances of higher institution students (HND and ND), teaching and non-teaching staff of Rufus Giwa Polytechnic Owo Ondo State Nigeria. It is therefore imperative to identify the accountability, fairness, ethical leadership on organizational performance of both staff and students.